Modular Approach to Select Bacteriophages Targeting Pseudomonas aeruginosa for Their Application to Children Suffering With Cystic Fibrosis - Krylov, Victor; Shaburova, Olga; Pleteneva, Elena; Bourkaltseva, Maria; Krylov, Sergey; Kaplan, Alla; Chesnokova, Elena; Kulakov, Leonid; Magill, Damian; Polygach, Olga (Frontiers in Microbiology, 2016)
This review discusses the potential application of bacterial viruses (phage therapy) towards the eradication of antibiotic resistant Pseudomonas aeruginosa in children with cystic fibrosis (CF). In this regard, several potential relationships between bacteria and their bacteriophages are considered. The most important aspect that must be addressed with respect to phage therapy of bacterial infections in the lungs of CF patients is in ensuring the continuity of treatment in light of the continual occurrence of resistant bacteria. This depends on the ability to rapidly select phages exhibiting an enhanced spectrum of lytic activity among several well-studied phage groups of proven safety. We propose a modular based approach, utilizing both mono-species and hetero-species phage mixtures. With an approach involving the visual recognition of characteristics exhibited by phages of well-studied phage groups on lawns of the standard P. aeruginosa PAO1 strain, the simple and rapid enhancement of the lytic spectrum of cocktails is permitted, allowing the development of tailored preparations for patients capable of circumventing problems associated with phage resistant bacterial mutants.